2008
DOI: 10.1093/pasj/60.sp2.s489
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Infrared 2.5—5μm Spectroscopy of Nearby Ultraluminous Infrared Galaxies with AKARI

Abstract: We report on the results of systematic infrared 2.5-5 µm spectroscopy of 45 nearby ultraluminous infrared galaxies (ULIRGs) at z < 0.3 using the IRC infrared spectrograph onboard the AKARI satellite. This paper investigates whether the luminosities of these ULIRGs are dominated by starburst activity, or alternatively, whether optically elusive buried active galactic nuclei (AGNs) are energetically important. Our criteria include the strengths of the 3.3 µm polycyclic aromatic hydrocarbon (PAH) emission feature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
173
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(185 citation statements)
references
References 64 publications
11
173
1
Order By: Relevance
“…Figures 2, 3, and 4 present Subaru, AKARI, and Spitzer infrared spectra of selected ULIRGs at z < 0.3, respectively (Imanishi et al, 2006;2008).…”
Section: Resultsmentioning
confidence: 99%
“…Figures 2, 3, and 4 present Subaru, AKARI, and Spitzer infrared spectra of selected ULIRGs at z < 0.3, respectively (Imanishi et al, 2006;2008).…”
Section: Resultsmentioning
confidence: 99%
“…The difference between these two correlations supports AGN activity contributing to L IR more than has thus far been considered to be the case. Also, considering the fact that there is no sign of departure for the ULIRG sample of Imanishi et al (2008) from the correlation between L PAH3.3 and L PAH6.2 (Figure 6), it is more likely to be L IR which causes the break. Recently, Yamada et al (2012) have found that the correlation between L PAH3.3 / L IR and L IR has a break around L IR ∼ 10 12 L from another MP of AKARI, MSAGN.…”
Section: The Pah 33 μM Emission As a Star Formation Indicatormentioning
confidence: 96%
“…Therefore, we look for the correlation between the combined sample of AMUSES and the literature samples. The large filled circles represent samples of AMUSES objects, while the small symbols represent samples from the literature (Rodríguez-Ardila & Viegas 2003;Imanishi et al 2008Imanishi et al , 2010Sajina et al 2009;Lee et al 2012). Note that L IR comes from Wu et al (2010).…”
Section: The Correlation Between L Pah33 and L Irmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the equivalent widths of the PAH features enable us to roughly estimate the star-formation contribution to the total L IR of a galaxy (Moorwood 1986;Roche et al 1991;Genzel et al 1998;Armus et al 2007;Imanishi et al 2007Imanishi et al , 2008Imanishi et al , 2010Veilleux et al 2009;Nardini et al 2008Nardini et al , 2009Nardini et al , 2010Pope et al 2008;Menéndez-Delmestre et al 2009;Coppin et al 2010;Stierwalt et al 2013Stierwalt et al , 2014, and more reliably estimate it when they are normalized with other spectral indicators (such as H 2 or [NeII] 12.8 µm line fluxes) or the slope of the IR continuum (Tommasin et al 2010). This approach is complementary to the one that uses spectral energy distribution (SED) fitting (e.g., Gruppioni et al 2016;Delvecchio et al 2014).…”
Section: Introductionmentioning
confidence: 99%